The Influence of Work Discipline, Organisational Culture, and Organizational Commitment on Employee Performance - Lestari, Sri; Suyono, Joko; Elisabeth, Darmasari Ratna; Suyono, Aldrin Arizona (Universitas Muhammadiyah Gresik, 2025)
This study aims to analyze the influence of work discipline, organisational culture, and organisational commitment on the performance of employees at the Surabaya Health Department. A quantitative research approach was used with a survey method. Data were collected through questionnaires distributed to 44 employees selected using purposive sampling. The data were analysed using multiple linear regression to examine the relationship between the independent variables (work discipline, organisational culture, and organisational commitment) and the dependent variable (employee performance). The results indicate that, simultaneously, work discipline, organisational culture, and organisational commitment significantly influence employee performance. Partially, work discipline and organisational commitment have a positive and significant impact, whereas organisational culture has a lesser effect. Among the three variables, organisational commitment has the most dominant influence on employee performance. This finding suggests that strengthening organisational commitment, such as increasing employee engagement, recognising contributions, and fostering a supportive work environment, is crucial for enhancing performance. Therefore, the Surabaya Health Department should prioritise strategies that reinforce organisational commitment to optimise employee performance.